Establishment of Village-Owned Enterprises Legality Process in North Sumatera: Establecimiento del proceso de legalidad de las empresas de propiedad de la aldea en el norte de Sumatera - RAMLAN, R.; KHAIRANI, L.; SIHOMBING, E.N.A.M. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACTThis paper aims to find out the number of village-owned enterprises that have problems with legality and knowing how the position of the village owned enterprise established without using village regulation. The research method is normative legal using the principles of the right approach.  This study sampled thirty village-owned enterprises. Data collection in this study is through interviews, observation, and documentation techniques. It can be concluded that the establishment of 27.6% of the village-owned enterprises do not have legal basis or do not meet the legal aspects. From these findings, practical strategic steps are essential to avoid continuing mistakes. RESUMENEl objetivo del estudio es averiguar el número de empresas pertenecientes a la aldea que tienen problemas con la legalidad y saber cómo se estableció su posición. El método de investigación es normativo legal utilizando los principios del enfoque correcto. Este estudio tomó una muestra de treinta empresas pertenecientes a la aldea. La recopilación de datos consiste en entrevistas, observación y documentación. Se puede concluir que el establecimiento del 27,6% de las empresas comunitarias no tiene una base legal o no cumple con los aspectos legales y los pasos estratégicos prácticos son esenciales para evitar errores continuos.